Pengaruh Mobilization With Movement terhadap Nyeri dan Lingkup Gerak Sendi Penderita Osteoarthritis Lutut di Rumah Sakit Islam Klaten - Sari, Dwi Rosella Komala; Kurniady, Devi Arhamevia; Perdana, Suryo Saputra (Faculty of Medicine, Universitas Andalas, 2023)
Osteoarthritis (OA) is characterized by pain that causes a decrease in knee joint range of motion, affecting a person's gait change and quality of life. Manipulation with Movement (MWM) is the most commonly used manual therapy technique in musculoskeletal disorders, especially in arthritis, to increase the range of movement (ROM).Â The MWM technique with a sliding direction aims to minimize pain and increase ROM in patients with knee OA. Objective: To determined the effect of MWM on pain and range of movement (ROM) in knee joint OA patients. Methods: This research was an experimental study with a quasi-experimental approach without a control group design. The research group consisted of 18 female patients who used the MWM technique two times a week for four weeks. The pain and ROM were measured by NRS and goniometer, respectively. Results: There were significant effects of MWM to reduce pain and increase ROM of knee joint (p<0.05). The average ROM of knee flexion and knee extension were improved by 12.2 and 1.7 degrees, respectively. The average pain was decreased by 2.4 as well after being treated by MWM for four weeks. Conclusion: MWM exercises were trained for four weeks to reduce pain and increase knee range of motion in flexion and extension in OA patients. MWM is recommended as an approach exercise for patients with knee OA to be involved in a rehabilitation program.Keywords: mobilization with movement, pain, range of joint movement, knee osteoarthritis